2013
DOI: 10.1021/es305330y
|View full text |Cite
|
Sign up to set email alerts
|

Cell Toxicity and Oxidative Potential of Engine Exhaust Particles: Impact of Using Particulate Filter or Biodiesel Fuel Blend

Abstract: The link between emissions of vehicular particulate matter (PM) and adverse health effects is well established. However, the influence of new emission control technologies and fuel types on both PM emissions and health effects has been less well investigated. We examined the health impact of PM emissions from two vehicles equipped with or without a diesel particulate filter (DPF). Both vehicles were powered either with diesel (B0) or a 50% v/v biodiesel blend (B50). The DPF effectively decreased PM mass emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 33 publications
4
49
0
Order By: Relevance
“…24,40,45,50 Although no universal pattern is observed, 11,24,25,40,43,49 many suggest that biodiesel particles may be more harmful to health than mineral diesel particles. For example, some older studies found that rapeseed biodiesel particles were more cytotoxic to mouse fibroblasts than mineral diesel particles, 25,42 and that particles collected from combusting an 80% mineral diesel : 20% biodiesel blend were more cytotoxic to human airway epithelial cells than either pure fuel alone.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…24,40,45,50 Although no universal pattern is observed, 11,24,25,40,43,49 many suggest that biodiesel particles may be more harmful to health than mineral diesel particles. For example, some older studies found that rapeseed biodiesel particles were more cytotoxic to mouse fibroblasts than mineral diesel particles, 25,42 and that particles collected from combusting an 80% mineral diesel : 20% biodiesel blend were more cytotoxic to human airway epithelial cells than either pure fuel alone.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…40,49 More recently, and using a relatively modern Euro IV engine, Gerlofs-Nijland et al (2013) demonstrated a greater toxic and pro-inflammatory capacity in human bronchial epithelial cells exposed to rapeseed biodiesel exhaust particles, compared with mineral diesel exhaust particles. 43 Another study showed that unspecified biodiesel particles in solution induced less apoptosis in human airway epithelial cells compared with mineral diesel particles in solution, 40 while Swanson and co-workers (2009) found that cytotoxicity was not consistently higher or lower in soybean biodiesel particle-exposed cells compared with mineral diesel-exposed cells. 51 Betha and co-workers (2012) exposed human epithelial carcinoma cells (A549) to particles extracted from the combustion of waste cooking oil-based biodiesel.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…A DPF absorbs most of these constituents and thereby, plays crucial roles in reducing diesel exhaust-derived disorders (Ristovski et al, 2012;Tsukue et al, 2010). A DPF effectively eliminates DPM and also decreases concentrations of aldehydes and polycyclic aromatic hydrocarbons (Gerlofs-Nijland et al, 2013;Young et al, 2012). As a result, use of DPFs has been effective to substantially improve the air environment of the Tokyo Metropolitan area (http://www.kankyo.metro.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies linked the increase in oxidative stress related to the use of FAME biodiesel fuels to a larger presence of oxygenated organic species in FAME aerosols than in petroleum-derived aerosols (Javala et al, 2012; Stevanovic et al, 2013). Also, Kooter et al (2011) and Gerlofs-Nijland et al (2013) found that particulates emitted by diesel engines fueled with neat and blended FAME biodiesel have similar oxidative potential but much higher cytotoxicity than particulates generated by the same engines fueled with petroleum diesel.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their favorable effects on DPM and some gaseous emissions, biofuels — primarily FAME biodiesels — were for some time used as high-biodiesel-concentration blends or neat as a strategy to reduce diesel emissions or the exposure of workers to those pollutants (Bugarski et al, 2012). The fact that diesel engines, when fueled with FAME biodiesels in place of ULSD, emit less total DPM by mass (Yuan et al, 2007; Sappok and Wong, 2008; Gerlofs-Nijland et al, 2013) was extensively exploited to reduce concentrations of diesel aerosols and gases in underground mines (Bugarski et al, 2010; Bugarski et al, 2014). In addition, FAME biodiesels were found to have favorable effects on carbon monoxide and hydrocarbon emission reductions (Schönborn et al, 2009; Hoekman and Robins, 2012; Bugarski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%